Influencias de las exigencias parentales en la relación docente – alumno de un niño de 10 años en 5to de básica - Camino Robles, Jennifer Nataly (2019)
The objective of this case study was to identify the influences of parental requirements in a 10-year-old child, having the father's death as one of the main findings in this case and how this affects the teacher-student relationship in the educational field and The social development of the child. Through the implementation of techniques such as the clinical interview and the medical history, it was possible to gather pertinent information, and with the help of the most appropriate tests, it allowed me to determine the diagnosis of Depression in the child to later use cognitive behavioral therapy and obtain a behavior change in it and that its educational and social development is the most appropriate